2013
DOI: 10.1111/zoj.12068
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular data confirm species assignment and dispersal of the genusLigia(Crustacea: Isopoda: Ligiidae) along northeastern coastal China and East Asia

Abstract: The morphological traits and mitochondrial genes of sympatric sea slaters from the genus Ligia were analysed from samples collected along northeastern coastal China and adjacent coastal East Asia to assign the species and to obtain interpretations of their distributions. Using 338 sequences and 199 diagnoses of 16S polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) from 331 specimens sampled from 26 localities, and homological sequences from counterparts from South Korea and the west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 47 publications
4
35
0
Order By: Relevance
“…Lastly, individuals from Cousine Island exhibit COI K2P divergences of 4.5–5.3% when compared to other localities (Mahé and Silhouette) within the inner islands. Interestingly, this pattern is similar to those previously reported for Seychellois herpetofauna from the inner islands (Rocha, Harris & Posada, 2011; Rocha, Posada & Harris, 2013; Silva et al, 2010) and to reports of cryptic diversity for other Ligia species, including L. occidentalis (Eberl et al, 2013; Hurtado, Mateos & Santamaria, 2010), L. hawaiensis (Santamaria et al, 2013; Taiti et al, 2003), L. baudiniana (Santamaria, Mateos & Hurtado, 2014), L. exotica and L. cinerascens (Yin et al, 2013), and L. oceanica (Raupach et al, 2014). The sum of our findings thus suggest the presence of 2–3 putative cryptic species of Ligia in the Seychelles: Aldabra Ligia being one, and those of Cousine and Silhouette + Mahé representing one or two putative species.…”
Section: Discussionsupporting
confidence: 89%
“…Lastly, individuals from Cousine Island exhibit COI K2P divergences of 4.5–5.3% when compared to other localities (Mahé and Silhouette) within the inner islands. Interestingly, this pattern is similar to those previously reported for Seychellois herpetofauna from the inner islands (Rocha, Harris & Posada, 2011; Rocha, Posada & Harris, 2013; Silva et al, 2010) and to reports of cryptic diversity for other Ligia species, including L. occidentalis (Eberl et al, 2013; Hurtado, Mateos & Santamaria, 2010), L. hawaiensis (Santamaria et al, 2013; Taiti et al, 2003), L. baudiniana (Santamaria, Mateos & Hurtado, 2014), L. exotica and L. cinerascens (Yin et al, 2013), and L. oceanica (Raupach et al, 2014). The sum of our findings thus suggest the presence of 2–3 putative cryptic species of Ligia in the Seychelles: Aldabra Ligia being one, and those of Cousine and Silhouette + Mahé representing one or two putative species.…”
Section: Discussionsupporting
confidence: 89%
“…Molecular studies of other Ligia species from North America and East Asia also revealed similar deep mitochondrial divergences (Jung et al ., ; Hurtado, Mateos & Santamaria, ; Markow & Pfeiler, ; Eberl, ; Eberl et al ., ; Yin et al ., ). In the case of Ligia occidentalis from the Pacific coast of North America, recent molecular studies also imply the existence of cryptic species (Eberl et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…and L. italica in the Mediterranean basin (Hurtado et al unpublished cinerascens extends further north into the Kuril Islands (Yin et al, 2013) (Eberl, 2013) and L. oceanica (Raupach et al, 2014). Within the L. exotica clade, Clade B, which is mostly restricted to temperate areas, exhibits comparatively lower genetic diversity (maximum K2P divergence = 2.0%) than clades C and D, which occur in warmer regions.…”
Section: Phylogeographical Patterns In East and Southeast Asiamentioning
confidence: 99%
“…leading Yin et al (2013) (2) determine whether further molecular diversity is found in these clades; and (3) shed light on the evolutionary and invasion history of L. exotica.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation